1988
DOI: 10.1007/bf00039884
|View full text |Cite
|
Sign up to set email alerts
|

Alternative carbohydrates promote differentiation of plant cells

Abstract: Corn syrups have been evaluated in media for embryogenesis, androgenesis and the production of secondary metabolites from plant tissue culture. In the systems examined, higher productivity was obtained with media containing corn syrups than with comparable media containing glucose or sucrose. Corn syrup did not increase growth of unorganized cell cultures. Increased productivity therefore reflects a syrup-mediated promotion of cell differentiation. The effects of corn syrup on increasing yields of secondary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
4
6
0
3
Order By: Relevance
“…Sucrose at 60 g l -1 gave the longest embryo (0.99 cm), compared to the other treatments followed by date syrup "Dibs" at 2 and 6% with significantly different. These results were in agreement with those obtained by some investigators [12,14] . Regarding fresh weight, data presented in Fig.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Sucrose at 60 g l -1 gave the longest embryo (0.99 cm), compared to the other treatments followed by date syrup "Dibs" at 2 and 6% with significantly different. These results were in agreement with those obtained by some investigators [12,14] . Regarding fresh weight, data presented in Fig.…”
Section: Resultssupporting
confidence: 94%
“…Kinnersley and Henderson [12] found that addition of corn (maize) syrup to basic culture media improves embryogenesis of wild carrot. In a comparison of the effects of adding coconut water, banana extract, pineapple juice or tomato juice to the Nitsch medium.…”
Section: Introductionmentioning
confidence: 99%
“…From the previous studies of Asemota et al (2007) they found that callus of date palm explants was initiated at 5 mg -l NAA from leaf explant when cultured in the Eeuwen's medium supplemented with NAA from 5-20 mg -l . Data presented here showed that, conversion of original somatic embryos enhanced strongly by added pollen palm extract without addition of NAA and BA (T4 and T3 treatments) this data insures the previous data obtained by Chen et al (2005) and Amo-Marco and Picazo (1994) who proved that adding plant extracts juice of coconut, tomato, potato, onion, banana, orange, apple, pineapple and yeast to the culture medium enhanced the growth of tissues, furthermore addition of corn (maize) syrup to basic culture media improves embryogenesis of wild carrot (Kinnersley and Henderson 1988). Use of other natural supplements like tomato juice, orange juice, malt extract, yeast extract, casein hydrolysate in the media for promoting multiplication and development of in vitro cultures have been demonstrated by many authors (Carimi et al, 1998on Citrus, Rahman et al, 2004and Aktar et al, 2007.…”
Section: Embryo Lengthsupporting
confidence: 89%
“…The origin of cultures of wild carrot (Daucus carota L.), cell line WC 63-2, and the culture media used to study anthocyanin accumulation and embryogenesis has been described by Kinnersly & Henderson [8]. The same reference describes the origin and culture conditions for suspension cultures of Nicotiana tabacum cv.…”
Section: Culturesmentioning
confidence: 99%